Exploring corporate social responsibility's global and Glocal practices in Qatar: A practitioner and stakeholder perspective - Ilaria Gualtieri; Martina Topić (Arab Economic and Business Journal, 2016)
This study analysed corporate social responsibility (CSR) in the state of Qatar, aiming to determine the discipline' global and glocal dimensions. The study investigated the notion that CSR remains western-driven in contrast to the scholarly trend that increasingly values national variables. Given the importance of CSR, the relationship between theory and contextual influences becomes a central element to evaluate the opportunity for specific corollaries to mainstream CSR. The methodology deployed for the study included a literature review, and interviews with practitioners and stakeholders. The results showed that although CSR as a concept is valid per se, an appropriate approach would value the operating environment as a key determinant, appreciating that specific cultural contexts necessitate variations to the mainstream theory.
Keywords: 650; Corporate social responsibility; Qatar; Stakeholder perspective; Practitioner perspective